Standard stake yield of 43 CMD cassava genotypes in 11 locations of Nigeria: implications for stem supply systems - Akoroda, M.O.; Yomeni, M.O.; Oyadiran, T.F.; Dixon, A.; Okoro, E. (2006)
Standard stake yield (SSY) was estimated using data from multi-locational trials in 11 locations. These were: Onne, Obrikom, Warri, Obayantor, Umudike, Nanka, Akure, Ajibode, Ibadan, and Zaria during 2003-2005 season. The aim was to identify location suitable for stem production and also to estimate the quantity of standard stakes obtainable per plant for all the 43 IITA- CMA resistant genotypes. Stakes of 25cm long cut from matured healthy plant were planted at 1mx1m on flat or ridges. No fertilizer was applied. About 5 to 8 stands depending of the location were considered to estimate the SSY per location. The average standard stake yield across the locations was 15.7 stakes. Akure had the highest SSY (25.4) followed by Onne (22.5) and therefore can be recommended as suitable location for stem production. Even though Obayantor (23.8) had a SSY greater than that of the mean (15.7), that location can be recommended only for the varieties tested there. In the case of Onne D, untimely operations and inefficient field practices are reduced the expected SSY.